A Study Consumers' Green Purchasing Intention - Cheah, Ching Mun (2009)
This research explores the factors that influence consumer behavior on buying green products. More specifically, this study examines the four dimensions such as environmental concern, social influence, self-image and man-nature orientation on the green purchasing behavior of students from College of Business, University Utara Malaysia. The total of 700 questionnaires were distributed, 604 questionnaires were returned and usable. Pearson correlation test showed that ‘self-image’ is the top influential factors in determining consumers’ green purchasing intention, followed by ‘social influence’. On the other hand, ‘environmental concern’ and ‘man-nature orientation’ is the third and fourth influential factors that determine green purchasing intention of consumers respectively. In this relation, marketers should consider these factors in carrying out appropriate promotions to attract customers.